Tailoring clinical management after embryo transfer using β-hCG levels in resource-limited settings - Swati Dhar; Prashanth Adiga; Anjali Mundkur; Vidyashree Ganesh Poojari; Pratap Kumar (Scientific Reports)
Abstract Cleavage-stage embryo transfers are often the best option for patients with limited oocytes or low fertilization rates due to medical or financial constraints. This study analyzed 424 women undergoing β-hCG testing 14 days after embryo transfer at a tertiary care center in India. Pregnancy outcomes were classified as no live births (biochemical pregnancies, ectopic pregnancies, miscarriages) or live births (single/multiple births). Higher β-hCG levels were associated with greater chances of live birth but also an increased risk of complications like preterm birth and preeclampsia, particularly in multiple pregnancies. A β-hCG threshold of 468 mIU/mL was identified as the optimal predictor of live birth, with 75% sensitivity and 72% specificity. Receiver operating characteristic (ROC) curve analysis confirmed its strong predictive value. By reducing the need for frequent monitoring, this single-test approach helps ease the emotional, financial, and logistical burdens patients face during IVF treatment. The study highlights β-hCG as a simple, cost-effective tool for providing early reassurance, guiding counseling, and personalizing follow-up, particularly in low-resource settings where access to fertility care remains challenging.